Fluid in the airway of nontraumatic death on postmortem computed tomography: relationship with pleural effusion and postmortem elapsed time - Ishida, Masanori; Gonoi, Wataru; Hagiwara, Kazuchika; Okuma, Hidemi; Shintani, Yukako; Abe, Hiroyuki; Takazawa, Yutaka; Ohtomo, Kuni; Fukayama, Masashi (The American journal of forensic medicine and pathology, 2014)
To evaluate radiographic features of endotracheal/endobronchial fluid in the airway (FA) observed on postmortem computed tomography (PMCT). We studied 164 subjects who died at our hospital between April 2009 and September 2012. Fluid in the airway was considered positive when fluid was identified in the lumen of 1 of the 2 main bronchi in continuity with a segmental bronchus. Pleural effusion and atelectasis/consolidation of the lung lower lobes were also evaluated. Fluid in the airway was observed in 60 (71%) of 84 subjects with unilateral or bilateral pleural effusion, and in 44 (55%) of 80 subjects without pleural effusion (P = 0.029). Of the latter, 41 (93%) had atelectasis/consolidation of the lower lung lobes. Among subjects without pleural effusion, average times after death to PMCT of subjects with and without FA were 501 and 314 minutes, respectively (P = 0.01). Time-course analysis showed that cases with FA on PMCT largely correlated with time after death (R = 0.7966). Fluid in the airway is frequently observed on PMCT in subjects with pleural effusion or atelectasis/consolidation of the lung. No FA in subjects without pleural effusion correlated to shorter times after death. In addition, FA frequency on PMCT increased over time after death.